A new species of anchovy, Encrasicholina sigma (Teleostei, Clupeiformes, Engraulidae), from Sulawesi, Indonesia - Hata, Harutaka; Motomura, Hiroyuki (Zootaxa, 2020)
The new anchovy Encrasicholina sigma n. sp. is described on the basis of 20 specimens collected from Sulawesi, Indonesia. Although the new species can be distinguished from all other congeners except for Encrasicholina pseudoheteroloba (Hardenberg 1933) by having a long upper jaw reaching to posterior margin of preopercle, dorsal and anal fins with two unbranched rays, an exposed bony urohyal, and spine-like scutes on the abdomen, E. sigma is distinguished from E. pseudoheteroloba by lower total gill-raker counts on the first, second, third, and fourth gill arches, and on the posterior face of the third gill arch (37–42, 31–35, 18–23, 16–20, and 4–7, respectively vs. 45–55, 34–45, 22–29, 19–25, and 4–9 in E. pseudoheteroloba) and a longer head (25.2–27.0% of SL vs. 22.8–27.5%) and shorter anal-fin base (12.9–14.8% of SL vs. 13.8–18.7%).